Global drug enforcement practical investigative techniques - Lee, Gregory D. 1953- (CRC series in practical aspects of criminal and forensic investigations, 2004)
It's a national epidemic and an international conspiracy. Drugs have infested our society with a vengeance, making the drug enforcement agent a central figure in the war on drugs. International training teams of the U.S. Drug Enforcement Administration (DEA) have traditionally taught the special skills required by all drug agents. Until now, there has never been a book for public consumption devoted strictly to this specialized field of criminal investigation.Global Drug Enforcement: Practical Investigative Techniques provides basic and advanced methods for conducting modern drug inves.